Tools for Knowledge and Learning: A Guide for Development and Humanitarian Organisations - and Ramalingam, Ben (ODI, 2006)
This toolkit presents entry points and references to the wide range of tools and methods that have been used to facilitate improved knowledge and learning in the development and humanitarian sectors.